FAKTOR PENGARUH KEMAMPUAN LEMPARAN (SHOOTING) PADA ATLET HANDBALL PUTRI JAWA TENGAH - Lusiana (Universitas Negeri Semarang, 2015)
This study on the factors that influence the outcome of the Throwing ability(Shooting) on the women's handball players in Central Java. This study aims to determine the relationship of anthropometric and physical characteristics specific to women's handball players in Central Java. throwing velocity was measured using a test instrument throws (Radar Gun passing Test), while anthropometric use instrumen tests BMI, arm length, arm circumference, arm and shoulder width range. Physical capabilities typically measured using test instruments Standing Long Jump, tests 30 Meter Sprint, tests flexibility (sit and reach), arm strength (Push Up) and Multistage Fitness Test (MFT) study using a sample of women players in Central Java (n = 82, mean SD age of 16.99 1.06 years and the experience of playing is 3.66 1.66). The results showed that the throwing velocity has a significant level (p <0.05) correlated with all variables except the calculated body mass index (BMI). This suggests that the ability to throw a handball athletes greatly influenced by anthropometric characteristics of good and excellent physical abilities.